Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

(Proof of (first) Isomorphism Theorem) Let $f : G \rightarrow H$ be a surjective group homomorphism. Let $K = \operatorname{ker} f$. Then the map $f' : G/K \rightarrow H$ by $f'(gK) = f(g)$ is well-defined and is an isomorphism. Proof: If $g'K = gK$, then $g' = gk$ with $k ∈ K$, and $f(g') = f(gk) = f(g) f(k) = f(g) e = f(g)$ so the map $f'$ is well-defined. It is surjective because $f$ is. For injectivity, if $f'(gK) = f'(g'K)$, then $f(g) = f(g')$, and $e_{H} = f(g)^{-1} · f(g') = f(g^{−1}) · f(g) = f(g^{−1}g')$ Thus, $g^{−1}g' ∈ K$, so $g' ∈ gK$, and $g'K = gK$. In summary, the normal subgroups of a group are exactly the kernels of surjective homomorphisms.

First of all, I am not getting how $f(g)^{-1} \cdot f(g')$ leads to $f(g^{-1}) \cdot f(g)$.

Secondly, I am unsure how the later part of the proof establishes injectivity.

And lastly, at, there is a diagram that shows the relationship, and can anyone explain this diagram with some insights from the above proof?

share|cite|improve this question
That diagram uses the concept of exact sequence. You can include the kernel and then factor by it and include this in $H$, since this factor is isomorphic to the image of $f$. – Sigur Aug 21 '12 at 0:21
There is a miss print. The correct is $f(g)^{-1}\cdot f(g')=f(g^{-1})\cdot f(g')$. – Sigur Aug 21 '12 at 0:24
If you show that $f(x)=f(y)$ implies that $x=y$ then $f$ is injective. – Sigur Aug 21 '12 at 0:26
@Sigur OK, but then why is $f(g)^{-1} = f(g^{-1})$? – Absolutio Zaka Aug 21 '12 at 0:26
Evidently there's a typo, it should read $f(g)^{-1}\cdot f(g')=f(g^{-1}\cdot f(g')=f(g^{-1}g')$. – Gerry Myerson Aug 21 '12 at 0:27
up vote 1 down vote accepted

For your first question, it is essentially assumed by hypothesis and the definition of $f'$ that $f(g')=f(g)$. But recall that for a homomorphism $f$, $f(g)^{-1}=f(g^{-1})$. This can be seen since $f(g^{-1})f(g)=f(g^{-1}g)=f(e_G)=e_H$, so $f(g^{-1})$ is indeed a left inverse for $f(g)$, and the same argument shows it is a right inverse. So just substitute to conclude $f(g)^{-1}\cdot f(g')=f(g^{-1})\cdot f(g)$.

Secondly, writing $x=gK$ and $y=g'K$, the proof shows that if $f'(x)=f'(y)$, then $x=y$. This is the standard method to show a function is injective. Another way to look at it is the equivalent statement that if $x\neq y$, then $f'(x)\neq f'(y)$. So $f'$ always takes distinct inputs to distinct outputs, that is, $f'$ is injective.

share|cite|improve this answer

I like to satate the next lemma to prove the first isomorphism theorem, if $f:G\longrightarrow H$ is a group morphism and $K\leq \ker f$ with $K$ normal subgroup of $G$, the map $\bar{f}:G/K\longrightarrow H$ given by $\bar{f}(gK)=f(g)$ is well defined and a group morphism and $\ker\bar{f}=\ker f/K$.

To prove that is well defined, let $gK=hK$ then $h^{-1}g\in K\subseteq\ker f$, so $f(h^{-1}g)=e$, from here $f(g)=f(h)$.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.